2010
DOI: 10.1177/0305735610377592
|View full text |Cite
|
Sign up to set email alerts
|

How music touches: Musical parameters and listeners’ audio-tactile metaphorical mappings

Abstract: Though the relationship of touch and sound is central to music performance, and audio-tactile metaphors are pertinent to musical discourse, few empirical studies have investigated systematically how musical parameters such as pitch height, loudness, timbre and their interactions affect auditory–tactile metaphorical mappings. In this study, 40 participants (20 musically trained) rated the appropriateness of six dichotomous tactile metaphors (sharp–blunt, smooth–rough, soft–hard, light–heavy, warm–cold and wet–d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 36 publications
6
55
1
7
Order By: Relevance
“…However, weight, elasticity and adhesion of solid objects may be thought of as similar to the viscosity of liquid objects, since they all directly relate to the resistance an object puts up to movement. Thus, based on the findings of Eitan and Rothschild (2010), Slobodenyuk et al (2015), Walker et al (2010) and Ward et al (2008), we can predict that high viscosity should be matched with low luminance and low pitch. Based on Slobodenyuk et al, the relationship between saturation and viscosity is likely to be non-linear -however, since we are using a two-alternative forced choice (2AFC) paradigm this relationship may not be apparent; rather, this CMC is likely to be weakly significant or nonsignificant (a non-significant result here may, of course, also indicate the lack of a CMC).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, weight, elasticity and adhesion of solid objects may be thought of as similar to the viscosity of liquid objects, since they all directly relate to the resistance an object puts up to movement. Thus, based on the findings of Eitan and Rothschild (2010), Slobodenyuk et al (2015), Walker et al (2010) and Ward et al (2008), we can predict that high viscosity should be matched with low luminance and low pitch. Based on Slobodenyuk et al, the relationship between saturation and viscosity is likely to be non-linear -however, since we are using a two-alternative forced choice (2AFC) paradigm this relationship may not be apparent; rather, this CMC is likely to be weakly significant or nonsignificant (a non-significant result here may, of course, also indicate the lack of a CMC).…”
Section: Introductionmentioning
confidence: 94%
“…However, the vast majority of research on CMCs involving tactile dimensions has been about solid objects, a summary of which we present in Table 1. There are also multiple studies on the effect Eitan and Rothschild (2010) Flute (compared to violin)/high sharpness Eitan and Rothschild (2010) of tactile dimensions on conceptual dimensions such as perceived expensiveness (e.g. Harrar and Spence, 2013;Ludden and Van Rompay, 2015), liking (Michel et al, 2015), femininity (Etzi et al, 2016) and activeness (Walker and Smith, 1985), which we do not include in the table.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multisensory interaction between hearing and touching is not unique to timbre: neurophysiological slipperiness between these sense modalities has been explained by the broad functional overlap of auditory and tactile sensory regions (Foxe et al, 2002;Schür-mann, Caetano, Hlushchuk, Jousmäki, & Hari, 2006). Eitan and Rothschild (2010) found that metaphors of tactile engagement are ubiquitous in listeners' conceptualization of pitch height, loudness, and timbre. Of these, timbre-particularly noisy timbre-is a uniquely transparent locus of tactile mapping, as reflected in common metaphoric vocabulary for qualities of sound (e.g., ''harsh,'' ''rough,'' ''coarse'') (Wallmark, 2014).…”
Section: Timbre Tactility and Metaphormentioning
confidence: 99%
“…Par exemple, Eitan et Rothschild (2010) ont testé la pertinence de métaphores tactiles pour la description des sons. Les participants à cette étude devaient évaluer la qualité sonore d'un ensemble de stimuli, variant en intensité, en hauteur et en timbre, suivant six échelles sémantiques bipolaires :…”
Section: Cerner La Chaleur Du Son Par La Psychoacoustiqueunclassified